Multiple cardiac papillary fibroelastomas: a case report and review of the literature - Ali, Mostafa; Alomari, Mohammad; El-Sayed Ahmed, Magdy M.; Garg, Pankaj; Pham, Anthony N.; Pham, Si M. (Frontiers in Cardiovascular Medicine, 2025)
Cardiac papillary fibroelastomas (PFEs) are the most common benign cardiac tumors and are typically solitary. PFEs affecting both sides of the heart are exceptionally rare, with only four cases reported in the literature. Herein, we report a case of a 63-year-old male presenting with signs and symptoms of embolic strokes and an embolism in the coronary arteries. An echocardiogram showed multiple masses on both the mitral and tricuspid valve leaflets. Because of the risk of embolism, he underwent successful valve-sparing surgical resection without complications. The follow-up echocardiogram at 6 months showed no recurrence and competence of both the mitral and tricuspid valves with minimal regurgitation.